HOXA9 mediates and marks premalignant compartment size expansion in colonic adenomas. (20th February 2019) - Janmaat, Vincent T; Liu, Hui; da Silva, Rodrigo A; Wisse, Pieter H A; Spaander, Manon C W; Ten Hagen, Timo L M; Smits, Ron; Bruno, Marco J; Fuhler, Gwenny M; Peppelenbosch, Maikel P
Abstract : Colonic polyps grow but remain benign for up to decades. Here we show that HOXA9 drives benign growth but simultaneously prevents further transformation. Abstract: The transformation of normal colonic epithelium to colorectal cancer (CRC) involves a relatively ordered progression, and understanding the molecular alterations involved may aid rational design of strategies aimed at preventing or counteracting disease. Homeobox A9 (HOXA9) is an oncogene in leukemia and has been implicated in CRC pathology, although its role in disease etiology remains obscure at best. We observe that HOXA9 expression is increased in colonic adenomas compared with location-matched healthy colon epithelium. Its forced expression results in dramatic genetic and signaling changes, with increased expression of growth factors IGF1 and FLT3, super-activity of the AKT survival pathway and a concomitant increase in compartment size. Furthermore, a reduced mRNA expression of the epithelial to mesenchymal transition marker N-cadherin as well as reduced activity of the actin cytoskeletal mediator PAK was seen, which is in apparent agreement with an observed reduced migratory response in HOXA9- overexpressing cells. Thus, HOXA9 appears closely linked with adenoma growth while impairing migration and metastasis and hence is both a marker and driver of premalignant polyp growth. Colonic polyps grow but remain premalignant for up to decades. Here, we show that HOXA9 drives growth in premalignant polyps, but simultaneously prevents further transformation.